Plan de mejora basado en lean-kaizen para el proceso de producción de un lubricante de PVCen una empresa de la industria colombiana (2020)
The purpose of this monograph is to set up an improvement plan on the production area's performance of a PVC lubricant in a Salt derived chemical Company. The plan is based on Lean Kaizen through the use of 5s and Kotter’s model, which come from Lean Manufacturing. The employed method consists of three stages. The first stage of the plan is aimed to diagnose the current state of the production area and compare them against the aspects on the 5S which have been already implemented, the second stage consists on the analysis of each step of the 5S method to figure improvement opportunities including the approaches according to these opportunities and the activities oriented to the implementation. The developed work shows that the Company and, specifically the area studied, exhibits a high percentage of fulfillment to the first three S of the improvement tool used as a base for this study’s development.